2020
DOI: 10.3390/ani10122384
|View full text |Cite
|
Sign up to set email alerts
|

A High Dietary Incorporation Level of Chlorella vulgaris Improves the Nutritional Value of Pork Fat without Impairing the Performance of Finishing Pigs

Abstract: The influence of a high inclusion level of Chlorella vulgaris, individually and supplemented with two carbohydrase mixtures, in finishing pig diets was assessed on zootechnical performance, carcass characteristics, pork quality traits and nutritional value of pork fat. Forty crossbred entire male pigs, sons of Large White × Landrace sows crossed with Pietrain boars, with an initial live weight of 59.1 ± 5.69 kg were used in this trial. Swines were randomly assigned to one of four dietary treatments (n = 10): c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 55 publications
(39 reference statements)
6
36
1
Order By: Relevance
“…For instance, piglets’ diet receiving 5% of C. vulgaris combined with the four-CAZyme mixture could be a valuable source of these protective fatty acids to both animals and humans. Consistent with our findings, the dietary C. vulgaris at this level of incorporation also produced an increment in n -3 PUFA amount in finishing pigs [ 9 ]. The enhancement of n -3 PUFA content subsequently resulted in a positive decline in n -6/ n -3 ratio in muscle with incorporation of C. vulgaris in piglets’ diet.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For instance, piglets’ diet receiving 5% of C. vulgaris combined with the four-CAZyme mixture could be a valuable source of these protective fatty acids to both animals and humans. Consistent with our findings, the dietary C. vulgaris at this level of incorporation also produced an increment in n -3 PUFA amount in finishing pigs [ 9 ]. The enhancement of n -3 PUFA content subsequently resulted in a positive decline in n -6/ n -3 ratio in muscle with incorporation of C. vulgaris in piglets’ diet.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the incorporation of this microalga led to higher content of pigments in the diets, in particular about 17 times more total carotenoids if compared with the reference diet. As highlighted by Coelho et al [ 9 ], the transfer of carotenoids from the microalga to the meat adds extra nutritional value to pork. Our data are in accordance with these authors, who also found 2 times higher total carotenoid contents in meat from finishing pigs fed with 5% of C. vulgaris .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations